The Paris-Lexington Road: Community-Based Planning And Context Sensitive Highway Design (Landscape Architecture Foundation Land and Community Design Case Study Series) - Schneider Krista L (Island Press, 2003)
Located in the heart of the Kentucky Bluegrass Region, the "Paris Pike" is a scenic, twelve-mile corridor running between Lexington and Paris. Beginning in 1969, the state of Kentucky sought to widen the road in order to improve safety and capacity. Various objections led to a federal court injunction imposed in 1979 that halted the project for more than fifteen years. Over the span of three decades, several consultant studies contributed to the public understanding of the road's significance and set the stage for what has been regarded as the model for context-sensitive road reconstruction in America.